Traces of primarily oral language in coordinate compound sentences with the conjunctions albo, ani and ale (based on Old Polish New Testament apocrypha) - Deskur, Aleksandra (Papers in Linguistics, 2025)
One of the hypotheses about primarily oral language that can be found in studies by orality and literacy scholars is that it is dominated by paratactic constructions rather than hypotactic ones. This hypothesis comes from Eric Havelock and Walter Jackson Ong, among others. The researchers, when writing about parataxis, considered only coordinate compound sentences with the conjunction i [and], without extending their reflection to other types of compound sentences and other markers of compounding. This article examines compound sentences excerpted from Old Polish New Testament apocrypha with other paratactic conjunctions: albo [or], ani [nor], and ale [but], respectively: alternative, disjunctive and adversative (according to the classification proposed by Leszek Bednarczuk in his book Polskie spójniki parataktyczne). Starting from the reflection of orality and literacy theoreticians as well as previous analyses of language historians, an attempt is made here to determine whether these constructions come into bundles with other traces of primarily oral language. These traces are identified with the help of a catalogue of traces of primarily oral language created for the purposes of the doctoral dissertation of the author, and verify them by taking into account additional factors typical of Old Polish material (genetic multilayered structure of text, dependence on the source, etc.).